Achieving Sustainable Development Goals (SDGs) In Africa: Challenges and Prospects - Kennedy Mahlatsi (The Thinker, 2021)
The implication of the 2030 Agenda for Sustainable development is that Africa’s structural transformation must be anchored by the principles of sustainable development. It is noted that Agenda 2030 does not provide political economy approach to understanding the genesis and cycles of poverty and inequality. The article further noted that Africa lags most significantly behind in its achievement of the SDGs, with a lower percent of countries achieving target by 2030 than any other region. Only limited progress towards achieving human development related SDGs is likely. However, due to their strong inclusivity focus, the SDGs present a better opportunity to involve more effectively different stakeholders. Achieving 2030 Agenda and Agenda 2063 calls for the African Union to focus more on implementation and follow up mechanisms, using monitoring frameworks that are robust enough to translate strategies into concrete development outcomes. The article argues that neoliberalism undermines the ability of developing countries in achieving sustainable development because of its emphasis in promoting the interest of the market at the expense of social and environment development. The article proposes the sustainable development model, which integrates economic, environmental and social objectives, to fully replace current growth-led models. To achieve pro-poor growth, countries must develop policies that have the potential of increasing growth and reducing poverty simultaneously. The article concludes that it is impossible to eradicate poverty without radically changing the system of global industrial capitalist production. In addition, Africa must develop holistic and all-encompassing approach with a view to achieving of SDGs while reformulating the short-term and mid-term policies during and the post-COVID period. Achieving the objective of eradicating extreme poverty and leaving no one behind by 2030 will be difficult if corruption and other development challenges are not seriously tackled.